COP26 campaign on Transforming Agricultural Innovation for People, Nature and Climate - CGIAR Research Program on Climate Change, Agriculture and Food Security (2020)
Part of the UK’s Nature campaign and led by FCDO, this campaign seeks to unlock billions for sustainable agriculture and was launched by Lord Goldsmith at the Climate Adaptation Summit.